Understanding the main drivers of value creation in an open innovation program - Herskovits, R.; Grijalbo, M.; Tafur, Javier (2013)
Innovation has been identified as the single most relevant element in fuelling corporations' competitive advantage and ultimate value creation. Corporations no longer rely on a single, linear structure of innovation; the new paradigm of open innovation opens up new possibilities of organizing innovation within the ecosystem, thus giving rise to new drivers for value creation. These value drivers have an impact on the strategic position of the firm and have the ability to create superior financial performance. In this paper we explore the close relationship between open innovation and value creation and propose a framework to analyze this process as well as the most critical elements involved. © 2013 Springer Science+Business Media New York.